2015
DOI: 10.1038/srep07618
|View full text |Cite
|
Sign up to set email alerts
|

A Pliable Electroporation Patch (ep-Patch) for Efficient Delivery of Nucleic Acid Molecules into Animal Tissues with Irregular Surface Shapes

Abstract: Delivery of nucleic acids into animal tissues by electroporation is an appealing approach for various types of gene therapy, but efficiency of existing methodsis not satisfactory. Here we present the validation of novel electroporation patch (ep-Patch) for efficient delivery of DNA and siRNA into mouse tissues. Using micromachining technology, closely spaced gold electrodes were made on the pliable parylene substrate to form a patch-like electroporation metrics. It enabled large coverage of the target tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Thus, the local delivery approach, i.e., electroporation, may have advantages over systemic delivery in accessible tumors. Successful gene silencing in different cells and tissues was obtained by using conventional electroporation as non-viral delivery approach of siRNA targeting reporter or therapeutic genes [5,21,[39][40][41][42][43][44]. Silencing therapeutic CD105 (endoglin), VEGF and Rho GTPase Rac1 genes demonstrated good antitumor and antivascular effects [5,21,45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the local delivery approach, i.e., electroporation, may have advantages over systemic delivery in accessible tumors. Successful gene silencing in different cells and tissues was obtained by using conventional electroporation as non-viral delivery approach of siRNA targeting reporter or therapeutic genes [5,21,[39][40][41][42][43][44]. Silencing therapeutic CD105 (endoglin), VEGF and Rho GTPase Rac1 genes demonstrated good antitumor and antivascular effects [5,21,45].…”
Section: Discussionmentioning
confidence: 99%
“…Another common permeation assistant strategy is the use of electroporation [36][37][38][39]. Electroporation employs a pair of electrodes than can be attached to the skin (Fig.…”
Section: Physical Routesmentioning
confidence: 99%
“…However, the effectiveness of topically administered therapeutic nucleic acids is often diminished by low permeation efficiency across the skin due to the pertinent protective physical barriers, including the stratum corneum, nucleated epidermal layers, and tight junctions [ 10 ]. Several previous studies have reported that, not only the physical methods, such as electroporation, microneedles, or iontophoresis [ 11 , 12 , 13 , 14 ], but also nanocarriers, such as liposome, polymer or carbon nanotube, are capable of penetrating siRNAs in animal skin [ 15 , 16 , 17 ]. Additionally, one expected method of improving siRNAs permeation efficiency is the use of the cell penetrating peptides, including the arginine-rich transcriptional activator (TAT)-derived peptides [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%